2014
DOI: 10.1142/s0219525914500209
|View full text |Cite
|
Sign up to set email alerts
|

Contextuality, Incompatibility and Biased Inference in a Quantum-Like Formulation of Computational Trust

Abstract: Trust models play an important role in computational environments. One of the main aims of the work undertaken in this domain is to provide a model that can better describe the socio-technical nature of computational trust. It has been recently shown that quantum-like formulations in the field of human decision making can better explain the underlying nature of these types of processes. Based on this research, the aim of this paper is to propose a novel model of trust based on quantum probabilities as the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…[50] argued that relevance is an operator on Hilbert space and as such is part of the quantum measurement process, neither was our insight totally unexpected. Rather, connected to the uncertainty principle, we see noncommuting measurements to surface also in information seeking as another link to quantum decision theory [51,52,53].…”
Section: Information Seeking Is Quantum-likementioning
confidence: 99%
“…[50] argued that relevance is an operator on Hilbert space and as such is part of the quantum measurement process, neither was our insight totally unexpected. Rather, connected to the uncertainty principle, we see noncommuting measurements to surface also in information seeking as another link to quantum decision theory [51,52,53].…”
Section: Information Seeking Is Quantum-likementioning
confidence: 99%
“…However, due to the uncertainty involved in this process, it is not prudent to presume that an agent is a liar by just interacting with him once. In general, the trustor's uncertainty about a partner decreases as the number of interactions between this partner and the trustor increases [Ashtiani and Azgomi 2014]. Therefore, we assume that the credibility of a source of information (σ s ) rely on the perceived uncertainty by the trustor, which can be estimated as follows:…”
Section: Experiments B: Trust Based On Shared Evaluationsmentioning
confidence: 99%
“…Sources of information with credibility lower than 0.8 are considered liars, and they are ignored by the trustor, such as shown in Figure 3 (b). Notice that, due to the uncertainty principle discussed previously [Ashtiani and Azgomi 2014], an agent playing as a source of information becomes unreliable over time as the number of lies told by him increases. Also, as it is possible to see in Figure 3 the society are telling lies, the trustor still considers some evaluations shared by lying agents as truths.…”
Section: Experiments B: Trust Based On Shared Evaluationsmentioning
confidence: 99%
“…Unitary transformations correspond to an individual's shift in perspective and relate one point of view to another. Recently, by using this mechanism Ashtiani and Azgomi introduced a quantum-like model of computational trust (Ashtiani and Azgomi, 2014). Trust, is one of the most widely used concepts in various areas of computational domain such as computer security, recommender systems and so on.…”
Section: What Can Quantum-like Modeling Bring To Computational Domains?mentioning
confidence: 99%
“…Quantum Bayesian inference as a generalized version of the classical Bayesian inference mechanism can play a key role in modeling more complex inferences in the computational domains. For example, we have shown that the quantum Bayesian inference can be used to model a biased inference mechanism in the context of computational trust (Ashtiani and Azgomi, 2014). Of course, this is only a preliminary research and lots of developments in a wide range of directions can be assumed for these mechanisms.…”
Section: What Can Quantum-like Modeling Bring To Computational Domains?mentioning
confidence: 99%